MANAJEMEN KESISWAAN DALAM PENDIDIKAN ISLAM BERBASIS MULTIPLE INTELLIGENCES - Mustajab Mustajab (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
The student’s management of Islamic Education based on Multiple Intelligences System (MIS) in PAUD Plus KB/TK Baitur Rohmah Jatiroto-Lumajang. The student input; without tests, the number of accepted enrollment is based on the capacity of the class esprovided for normal children and Children with Special Needs (ABK), then held test of Multiple Intelligences Research (MIR). The process of learning; teachers designed lesson plan based on the results of MIR and SOP, implement learning with multiple intelligences strategy-based the brain works, and valuated/assessed students' competencies are accompanied by a consultant education. Other than teaching, teachers continue to upgrade themselves through some professional development programs. Students output; student competence including cognitive, psychomotor, and affective domains were evaluated using the authentic assessment that focuses on ipsative- discovery ability.